PENGEMBANGAN PARADIGMA WAKAF HAK ATAS TANAH DI INDONESIA SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Rochmiyatun, Siti (Universitas Islam Negeri Raden Fatah Palembang, 2017)
Waqf land is a recommended implementation of Islamic worship, which has social and economic aspects for the community. Waqf paradigm of land in the community becomes one of the obstacles in advancing Waqf in Indonesia. The development of paradigms such as Waqf should be in writing, professional management appointments, more productive, the development of object types and their allocation, the exchange of waqf objects, the pattern of selection of waqf objects, and pledges of endowments aimed at the general public. Therefore, the development of land paradigm of Waqf should always refer to the principles of Islam. Such management in the community is a strategic step for the development and development of Waqf, in order to achieve and improve the welfare of the community.